Pengaruh Budaya Sekolah Terhadap Kinerja Guru Di SMPN 3 Baso - Nur Arifin; Kurniati Karim; Akhir Lusono; Trisna Rukhmana; Abdi Sakti Walenta; M. Rusdi (Departement of Mathematics Education, 2023)
Identification of the problems in this study were teachers who did not prepare lesson plans such as lesson plans and syllabus, teachers did not use learning media / visual aids in carrying out the learning process, teachers came late to school. This research is aimed at teachers of SMPN 3 Baso. The purpose of this research is to describe data about the influence of school culture on teacher performance at SMPN 3 Baso. This type of research is survey research with a quantitative approach to prove the influence of school culture on teacher performance. This research is also known as population research. The sampling method is that the entire population is sampled because the number of samples is less than 100, namely 20 people. Data collection techniques by distributing questionnaires using a Likert scale. The alternative answers are